2023
DOI: 10.1021/acs.chemmater.3c00493
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism and Excitonic Luminescence of Supercritical-Fluid-Synthesized ZnO Nanoparticles

Abstract: Extensive research on nanosized ZnO has proven that its optical properties are challenging to control due to a number of possible defects producing various emissions in the visible range. Our group proposed a low-temperature, supercritical-fluid-driven synthesis of isotropic nanosized particles that exhibit a unique and unprecedentedly pure excitonic emission, comparable to that of single crystals. The present article reports the growth mechanism at the origin of the unexpectedly pure excitonic emission as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…The binding of aminoalcoholate ligands to the ZnO surface results in the substantial spectral differences due to the core–ligand interactions, and the most pronounced differences in the spectra of QDs and proligands are observed in the two regions, i.e., 350–500 and 950–1150 cm –1 . The low wavenumber region is characteristic for the ZnO modes ,, and thus is especially important for the analysis. The second region is dominated by the coating aminoalcoholate ligand vibrations , and contains the most intensive bands observed for all studied ligands (Figure and Figure S21), but in some instances, the ZnO combination modes and overtones are present .…”
Section: Resultsmentioning
confidence: 99%
“…The binding of aminoalcoholate ligands to the ZnO surface results in the substantial spectral differences due to the core–ligand interactions, and the most pronounced differences in the spectra of QDs and proligands are observed in the two regions, i.e., 350–500 and 950–1150 cm –1 . The low wavenumber region is characteristic for the ZnO modes ,, and thus is especially important for the analysis. The second region is dominated by the coating aminoalcoholate ligand vibrations , and contains the most intensive bands observed for all studied ligands (Figure and Figure S21), but in some instances, the ZnO combination modes and overtones are present .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Al 2 O 3 –SiO 2 binary glass prepared through the sol–gel process has a low preparation temperature (below 700 °C), and the glass samples have high purity and uniform composition distribution compared to those in the preparation temperature of 1500 °C by the melting process. Previous research has shown that aluminum lactate, which is a precursor to alumina, can be used to make alumina-containing glass in a silicon-containing/silicon-free environment. Additionally, by altering the pH of the sol solution, uniform and clear xerogels may be obtained using the chelated lactic acid ligand. , Lead sulfide (PbS) colloidal quantum dots (CQDs) with a wide exciton Bohr radius and a small bandgap show the advantage of producing light at wavelengths ranging from visible to mid-infrared. Moreover, PbS CQDs provide variant nonlinear optical (NLO) responses. In NIR, PbS CQDs exhibit saturable absorption, which can be exploited as a Q-switcher or passive mode-locker for NIR lasers. , The ionic precursor of PbS quantum dots may be evenly disseminated using the broad doping concentration adjusted across a wide gradient in the sol–gel process, which is an unmatched benefit of this approach compared to that of the conventional melting method.…”
Section: Introductionmentioning
confidence: 99%